Analisis Pengaruh Transformational Leadership Terhadap Produktivitas Kerja - Ferdy Leuhery; Heriswanto Heriswanto; A. Ary Setyawan; Agus Suyatno; Carolina Ety Widjayanti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Transformational leadership is a leadership style that has long been discussed in the context of management and organization. The purpose of this study was to analyze the effect of transformational leadership on work productivity. The research method used is a literature study or Library Research with a qualitative approach. The aim is to analyze the comparison of theories about the differentiation between current ratio and profitability ratio on the company's stock price with the help of related references in the literature review. Based on the literature review that has been carried out on the results and discussion from both national and international journals, the conclusions in this article are: Transformational Leadership affects Work Productivity. Good leadership in the form of Transformational Leadership is essentially able to improve the quality and productivity of employee performance in a work environment. Keywords: Transformational leadership, work productivity